Traumatic superficial temporal artery pseudoaneurysm: Successful management using endovascular embolization - Ali Alkhaibary, MBBS; Ahoud Alharbi, MBBS; Noura Alsubaie, MBBS; Noor Alghanim, MBBS; Sami Khairy, MBBS; Nabil Ozair, MBBS; Laila Baydhi, MBBS; Fahd Musawnaq, MBBS; Makki Almuntashri, MBBS; Abdulaziz Alarifi, MBBS; Mohammed Alwohaibi, MBBS; Ahmed Aloraidi, MBBS; et al. (Radiology Case Reports, 2022)
Superficial temporal artery pseudoaneurysms are uncommon but can be potentially life-threatening. Considering their rarity, the present article outlines the clinical presentation, radiological findings, intervention, and outcome of traumatic pseudoaneurysm of the superficial temporal artery. An 83-year-old female sustained a traumatic injury to the temple, resulting in right-sided swelling of the forehead. Brain computed tomography and cerebral angiogram revealed a right-sided homogenously-enhancing pseudoaneurysm in the frontal region. Successful occlusion of the lesion was achieved utilizing endovascular embolization. Three months after discharge, the patient reported no complaints or recurrence. Subsequent management included reassurance and observation with periodic clinical assessments. The unusual presentation of superficial temporal artery pseudoaneurysms requires clinicians to have thorough knowledge on the clinical presentation, proper steps in diagnosis, and the approach of choice in management. Endovascular embolization of superficial temporal artery pseudoaneurysms remains a valid approach to achieve successful occlusion of the lesion.